AB0436 All The "Hispanics" Are Not Equal. The Severity and Activity of Patients with SLE Is Higher in Mestizos Latin American vs. European Caucasian. Lessons from Relesser. (15th July 2016) - Hernández-Cruz, B.; Alonso, F.; Calvo Alén, J.; Pego-Reigosa, J.M.; Lόpez-Longo, F.J.; Galindo Izquierdo, M.; Olive, A.; Tomero, E.; Rúa-Figeroa, Í.; ,
Abstract : Background: SLE is a known disease for the study of ethnic and gender minorities. In Spain, from 1998 to 2011, occurred a significant immigration from Latin American people. The English speakers consider "Hispanics" as the same ethnic group. But there are differences between the Hispanics from Spain (with ethnicity European Caucasian) and the Hispanics from Latin America (with ethnicity Mestizo Latin American). Objectives: To know the demographic, clinical, severity, activity, damage, mortality and comorbidity of SLE in Hispanics with ethnicity European Caucasian (EC) and in Hispanic Mestizos from Latin American (MLA) residents in Spain. To identify differences between the groups. Methods: Design: observational, multicentric, crossover study. Patients with SLE (ACR 1987) and <16 years old were included in 45 rheumatology Units in Spain. The RELESER methodology has been informed. Statistical analysis: we grouped the patients from the registry in two groups: EC and MLA and descriptive, univariate and multivariate statistics were done. Results: 3, 490 patients with SLE were included, 90% females; 3, 305 (92%) Hispanics EC y 185 (5%) Hispanics MLA. The Table shows the main variables. Patients MLA had higher levels of activity (SLEDAI), severity (KATZ INDEX) and number of admissions to the hospital for SLE activity. The damage index (SLICC), mortality, and comorbidity Index showed no differences. In the multivariate analysis several models were constructed with adjusted for age, sex and disease duration. The patients MLA had a higher risk for Severity (Katz Index >3) OR 1, 45 (1, 038 – 2, 026, p=0, 02. This differences were not found for activity: OR 0, 98 (0.30 - 1.66), may be for collinearity. Conclusions: The SLE of Hispanics MLA patients had clinical differences when it was compared with Hispanics EC patients, mainly higher severity and activity. This shows that all the Hispanics are not equal. Disclosure of Interest: None declared